Profile of Immunoglobulin G N-Glycome in COVID-19 Patients: A Case-Control Study - Hou, Haifeng; Yang, Huan; Liu, Pengcheng; Huang, Changwu; Wang, Meng; Li, Yuejin; Zhu, Mingsong; Wang, Jing; Xu, Yuan; Wang, Youxin; Ma, Qingwei; Li, Dong; et al. (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) remains a major health challenge globally. Studies suggested that changes in glycosylation of IgG are closely associated with severity of COVID-19. This study aimed to compare the profiles of IgG N-glycome between COVID-19 patients and healthy controls. A case-control study was conducted, in which 104 COVID-19 patients and 104 age- and sex-matched healthy individuals were recruited. Serum IgG N-glycome composition was analyzed by hydrophilic interaction liquid chromatography with ultra-high-performance liquid chromatography (HILIC-UPLC) approach. COVID-19 patients have a decreased level of IgG fucosylation, which upregulates antibody-dependent cell cytotoxicity (ADCC) in acute immune responses. In severe cases, a low level of IgG sialylation contributes to the ADCC-regulated enhancement of inflammatory cytokines. The decreases in sialylation and galactosylation play a role in COVID-19 pathogenesis via activation of lectin-initiated alternative complement pathway. IgG N-glycosylation underlines the complex clinical phenotypes of SARS-CoV-2 infection.